The Influence Of Job Achievement, Education, Training And Competencies On Employees' Career Development At The Lahat District Dprd Secretariat Office - Ilpiyano, Marko; Lokhisika , Lokhisika; Hidayah, Restu (Social Sciences Journal, 2024)
This research aims to determine and analyze the influence of Job Performance, Education, Training and Competency on Employee Career Development at the Lahat Regency DPRD Secretariat Office, either partially or simultaneously. This research uses a quantitative research method with respondents, namely employees of the Lahat Regency DPRD Secretariat Office, totaling 48 respondents. Testing in this research used multiple linear regression analysis with SPSS (Special Package and Service Solution) version 26 program tools. The results of the research show that Job Achievement, Education, Training and Competency are proven to have a significant influence on Employee Career Development at the Lahat Regency DPRD Secretariat Office both partially and simultaneously